2020
DOI: 10.1186/s12968-020-00629-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac structural changes after transcatheter aortic valve replacement: systematic review and meta-analysis of cardiovascular magnetic resonance studies

Abstract: Background Transcatheter aortic valve replacement (TAVR) is increasingly used to treat patients with severe aortic stenosis (AS). Cardiovascular magnetic resonance imaging (CMR) provides reliable and reproducible estimates for assessment of cardiac structure and function after TAVR. The goal of this study was to conduct a systematic review and meta-analysis of the literature to assess left ventricular (LV) volumes, mass and function by CMR after TAVR. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Left ventricular remodelling occurs after TAVI, with reductions in left ventricular end-diastolic volume index, end-systolic volume index, left ventricular mass index, and increased LVEF. 34 Abu Khadija et al showed that the reduction of the NLR as an inflammatory marker after TAVI in group with reduced left ventricular function caught up with the NLR in patients with preserved left ventricular function after 6 months of follow-up. 26 Condado et al showed that elevated NLR and plateletlymphocyte ratio (PLR) are associated with a higher Society of Thoracic Surgeons -Predicted Risk of Mortality (STS-PROM) score.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular remodelling occurs after TAVI, with reductions in left ventricular end-diastolic volume index, end-systolic volume index, left ventricular mass index, and increased LVEF. 34 Abu Khadija et al showed that the reduction of the NLR as an inflammatory marker after TAVI in group with reduced left ventricular function caught up with the NLR in patients with preserved left ventricular function after 6 months of follow-up. 26 Condado et al showed that elevated NLR and plateletlymphocyte ratio (PLR) are associated with a higher Society of Thoracic Surgeons -Predicted Risk of Mortality (STS-PROM) score.…”
Section: Discussionmentioning
confidence: 99%
“…3 TAVI can potentially induce reverse remodelling, which can lead to structural and functional improvements. 5,6 Treating patients earlier in the AS disease course may help limit diastolic dysfunction and potentially reduce the negative impact of HFpEF. Valvular heart disease, such as AS, may mimic HFpEF, making the diagnosis of HFpEF particularly challenging in this context.…”
Section: Discussionmentioning
confidence: 99%
“…3 Transcatheter aortic valve implantation (TAVI) has been shown to potentially induce a process of reverse remodelling leading to structural and functional improvements. 5,6 A substantial proportion of TAVI patients may have underlying heart failure with preserved ejection fraction (HFpEF) in addition to AS, due to the fact that both entities share common risk factors, such as age, hypertension, diabetes and chronic kidney disease. 7,8 Although mortality and heart failure hospitalization rates of patients with HFpEF are known to be high, the prognostic implications of HFpEF are not adequately reflected by current risk prediction models, such as the Society of Thoracic Surgeons score (STS) and guidelines for the management of patients undergoing TAVI.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, especially cardiovascular magnetic resonance (CMR) imaging is of growing importance as an appropriate non-invasive tool for comprehensive myocardial analyses including strain and tissue analyses. Previous CMR studies have demonstrated detection of volumetric functional improvement following TAVR and recently applied CMR imaging to identify dynamic structural changes of myocardial compartments assessing reverse myocardial remodeling and recovery from AS [ 10 , 11 ]. Importantly, CMR imaging allows non-invasive assessment of myocardial fibrosis, which is of growing relevance as another parameter for ventricular failure in AS patients and possesses important prognostic informations [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%